THE EFFECT OF EMPLOYEE RECRUITMENT SYSTEM AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE CV. KARUNIA JAYA (A3 Fresh O2) BONDOWOSO REGENCY - Lisa Sukmawati; Dewie Tri Wijayati Wardoyo; Anang Kistyanto (SEAN Institute, 2023)
This study aims to analyze the effect of the recruitment system on employee performance and the work environment on employee performance. The sample in this study were permanent employees of CV Karunia Jaya (A3 Fresh O2) Bondowoso Regency using random sampling techniques on employees, and data collection was carried out through observation, distributing questionnaires, and interviews. The method used in this research is quantitative, while the data is analyzed using SPSS. The results of this study indicate that the recruitment system has a positive and significant effect on employee performance. Furthermore, the work environment has a positive and significant effect on employee performance, and there is a relationship between employee recruitment system variables and work environment variables that simultaneously affect employee performance variables.